'Relieving gloomy and objectless lives'. The landscape of Caterham Imbecile Asylum. (17th August 2016) - Eastoe, Stef
Abstract: From the mid-eighteenth century the lunatic asylum landscape has been recognised as playing a key role in the health of patients. This article explores the landscape of a different type of nineteenth-century institution, Caterham Imbecile Asylum, one of the first state imbecile asylums. Built following the public health reforms of the 1860s, Caterham was a long-stay institution, and thus developed a particular institutional geography, due to the nature of its patients and its remit. This article will examine how the landscape of Caterham, its location, its grounds and its wider environment, were used as part of the asylum regime to provide a therapeutic landscape, and relieve the formerly gloomy, monotonous and objectless lives of its patients.